2004
DOI: 10.1073/pnas.0403621101
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB activation in human breast cancer specimens and its role in cell proliferation and apoptosis

Abstract: Lack of molecular targets in estrogen receptor-negative (ER-negative

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
340
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 434 publications
(367 citation statements)
references
References 39 publications
22
340
0
5
Order By: Relevance
“…Figure 6A shows the characterization of ER expression by WB (left panel) and activity, mirrored by progesterone receptor (PGR) expression as evaluated by qRT-PCR (right panel). In accordance with the literature, 19 a higher transcriptional activity of NF-kB was observed in ER− cell lines (HCC1954, SKBr3, and MDAMB453) than ER+ lines (BT474, MDAMB361, and ZR75.30) (Figure 6B). Hence, CCL2 mRNA and protein levels were higher in ER− than ER+ cell lines (Figure 6C).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Figure 6A shows the characterization of ER expression by WB (left panel) and activity, mirrored by progesterone receptor (PGR) expression as evaluated by qRT-PCR (right panel). In accordance with the literature, 19 a higher transcriptional activity of NF-kB was observed in ER− cell lines (HCC1954, SKBr3, and MDAMB453) than ER+ lines (BT474, MDAMB361, and ZR75.30) (Figure 6B). Hence, CCL2 mRNA and protein levels were higher in ER− than ER+ cell lines (Figure 6C).…”
Section: Resultssupporting
confidence: 91%
“…Accordingly, tumors dependent on HER2 signaling and classified by our TRAR model as responsive to trastuzumab treatment (TRAR-low) were found to express higher levels of CCL2 and to be more infiltrated by CD68+ cells than non-HER2 addicted, trastuzumab resistant (TRAR-high) tumors. This supports the reported concept that trastuzumab, through its constant fragment Fc, mediates anti-tumor cytotoxic effects by rendering tumor cells recognizable by macrophages 7,19 other than NK cells. Results obtained in an animal model using an anti-CCL2 monoclonal antibody, which indicated improved monocyte/macrophage (CD11b+ F4/80+) infiltration in the TME associated with higher trastuzumab anti-tumor inhibitory activity, supported the role of these immune cells in trastuzumab efficacy.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings in prostate tumorigenesis are consistent with previous observations in other cancer types, such as gastric (Sasaki et al, 2001), uterine cervix (Nair et al, 2003), colorectal (Yu et al, 2003), breast (Biswas et al, 2004), and head and neck squamous cell cancers , showing that NF-kB activation occurs mainly in established cancer tissues rather than in normal or premalignant lesions. In the present study, NF-kB staining was not significantly linked to other known prognostic factors of biochemical relapse such as preoperative PSA levels, surgical margins or Gleason grade.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with this, the RelA subunit was detected as nuclear in approximately 16% of primary breast cancers. On the other hand, Biswas et al (2004) reported that the p50/RelA heterodimer is activated in the majority (86%) of estrogen receptor (ER)-negative, ErbB2/Her2-positive breast tumors. However, since elevated ErbB2 expression occurs in approximately 20-25% of breast tumors, the above results suggest that the activation of RelA is not widely prevalent in primary breast tumors but may be associated more with distinct subtypes (i.e., Her2 positive/ER negative).…”
Section: Breast Cancermentioning
confidence: 99%